Elementary School Size and Differences in Student Progress by Gender: A Texas, Multiyear Statewide Analysis - Busby, Amy C.; Martinez-Garcia, Cynthia; Slate, John R. (Journal of Interdisciplinary Studies in Education, 2021)
In this investigation, the degree to which student enrollment (i.e., school size) at elementary schools was related to student progress on the State of Texas reading and mathematics state-mandated assessments was examined for boys and for girls. Archival data available on the Texas Academic Performance Report were analyzed for the 2013-2014, 2014-2015, 2016-2017, and 2017-2018 school years. Inferential analyses revealed the presence of statistically significant differences, with below small to small effect sizes. Large-size schools had statistically significantly higher progress rates in reading than Small-size schools for boys and for girls. Large-size schools also had statistically significantly higher progress rates in mathematics for boys than Small-size schools. Results for progress rates in mathematics for girls was varied. Implications for policy and practice, as well as recommendations for future research, are provided.